Removal of Ammonium ions and Phosphates ions from aqueous solutions using biochar as an adsorbent and recovery of them as fertilizers - Pantoja Alvarez Fernanda Liceth; László Zsuzsanna; Beszédes Sándor (2025)
In general, domestic wastewaters contain huge amount of ammonium and phosphates which are components known to cause eutrophication, and should be removed. However, these compounds could be utilized as fertilizers too. Biochar can remove a wide range of pollutants from water, because of this, it is important to study the physical–chemical properties to predict the behaviour of the biochar adsorbent in contact with adsorbates. Thus, this study aims to investigate the impact of the feedstock and the produce biochar conditions, additionally to determine the efficiency of biochar as an adsorbent of ammonium in aqueous solutions in the presence of organic compounds of typical dairy wastewaters and in presence of phosphates. Banana leaves and poplar chop were the feedstock used for produce biochars samples, 300, 400 and 500 °C were the pyrolysis temperature; non-modification, alkali modification and acidic modification were the conditions for pretreat the material before pyrolysis process. The characterization of all biochars samples were carried out through zeta potential analysis, scanning electron microscopy, energy dispersive X-ray spectroscopy (SEM–EDX), Fourier transform infrared spectroscopy, and specific surface area measurements. The adsorption properties of biochars were evaluated by Batch experiments, germination and planting experiments were performed for used the recovery biochar enhanced with nutrients. The results demonstrated that the pyrolysis temperature has a large impact on the yield, structure, elemental composition, and surface chemistry of the biochar. Considering the non-modified condition, biochar prepared at 300 °C is the most efficient for NH4+ adsorption, achieving a capacity of 7.0 mgNH4+/g of banana-derived biochar used and 4.38 mgNH4+/mg of poplar chop biochar. Alkali modification enhanced the adsorption capacity results and acidic modification does not influence significantly in the adsorption capacity. The Temkin isotherm model fits better the experimental data of poplar chop-derived biochars. On the other hand, Harkins–Jura isotherm model fits the experimental data best for banana leaves-derived biochars samples.
Disszertacio
Keywords: környezettudományok; Vízbázisok; Természeti erőforrások kutatása és kiaknázása